2017
DOI: 10.3390/app7080810
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Tolerance and Inactivation of Escherichia coli recovered from Wastewater Treatment Plants in the Eastern Cape, South Africa

Abstract: Featured Application: This study examined the tolerance of Escherichia coli isolates, a fecal indicator of water contamination, to chlorine as a common water disinfectant and the effectiveness of chlorine at different concentrations in eliminating E. coli in wastewater effluent. Data obtained can be used as baseline monitoring data for future epidemiological surveillances that could further enhance the control of E. coli and some bacteria species of public health concern in wastewater treatment plants and ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…The final effluent compliance was about 3.57% when measured against zero E. coli count/100 mL of the special limit. The high free chlorine concentration detected confirmed that the dosed chlorine was more than sufficient and possibly indicated the presence of chlorine resistant strains [ 18 ]. The presence of resistant microorganisms pose significant risk to public health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final effluent compliance was about 3.57% when measured against zero E. coli count/100 mL of the special limit. The high free chlorine concentration detected confirmed that the dosed chlorine was more than sufficient and possibly indicated the presence of chlorine resistant strains [ 18 ]. The presence of resistant microorganisms pose significant risk to public health.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of resistant microorganisms pose significant risk to public health. Studies have shown stress mechanisms [ 18 , 42 , 43 ] and resistance genes mechanisms [ 44 , 45 ] advancing in the resistance of E. coli to disinfection by chlorine. As the final effluent samples, the samples collected prior to disinfection were also analyzed to determine the number of organisms expected to be eradicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous review found that the most commonly tested organisms were in the class Gammaproteobacteria in the genus Escherichia . Escherichia was likely tested most often because it is a model bacterial organism and because it is a common fecal contamination indicator used in water treatment [ 100 , 101 ]. Pseudomonas was identified as the next most commonly used organism in the previous semi-systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…To control of E. coli and curli fiber contamination, several controls and environmental precautions will be put in place, as discussed in Table 2. As a further precautionary measure, E. coli contamination will be detected using standard methods and the water will be treated with 1.5 mg/L of chlorine, a potent disinfectant [18].…”
Section: Discussionmentioning
confidence: 99%